Rationalizing and Disrupting Fluxional Processes in Agostically Stabilized 14-Electron Alkyliridium Hydride Complexes - Phillips, N; Treasure, L; Rees, N; Tirfoin, R; McGrady, J; Aldridge, S (Wiley, 2014)
We have investigated the fundamental patterns of reactivity for the cationic IrIII complexes [(6-Mes)(6-Mes′)Ir(H)]+ and [(7-Mes)(7-Mes')Ir(H)]+ [6-Mes, 7-Mes = ring-expanded N-heterocyclic carbene (NHC) ligands, ' indicates that NHC is tethered through an iridium-bound CH2 group], each of which undergoes degenerate fluxional exchange between an iridium-bound agostic C-H bond and the discrete alkyl/hydride ligands resulting from C-H activation. A comparison between the activation parameters ΔH‡ and ΔS‡ determined by variable-temperature NMR (VT-NMR) spectroscopy line-shape analysis and those obtained from DFT calculations on model systems offers a basis to discriminate between different possible exchange mechanisms, and an oxidative addition pathway gives the lowest barrier and also the best agreement between experiment and theory. The addition of neutral Lewis base donors to [(6-Mes)(6-Mes')Ir(H)]+ resulted in the displacement of the weak agostic C-H⋯Ir interaction and the generation of static (alkyl)iridium(III) hydride complexes such as [(6-Mes)(6-Mes')Ir(H)(CNtBu)2]+. The analogous carbonyl complex is more labile, with the enhanced π-acceptor properties of the ancillary ligands leading to C-H reductive elimination and to the formation of the IrI complex [(6-Mes)2Ir(CO)2]+, which incorporates unactivated NHC donors and has the ability to reversibly take up H2.